Analisis Tingkat Perputaran Modal Kerja dan Implikasinya Terhadap Likuiditas PT.Pinago Tbk Periode 2017-2019 - Amelia Sagita Pebrianti; Harsi Romli; RM Rum Hendarmin (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
This study aims to analyze the level of working capital turnover and liquidity of PT. Pinago Tbk in 2017-2019. The data used is secondary data sourced from the company's financial statements. Qualitative descriptive analysis techniques are applied in this research. To analyze working capital turnover using several measurement methods, namely cash turnover (CTO), account receivable turnover (ARTO), inventory turnover (ITO), and net working capital (NWC). Meanwhile, to analyze the liquidity ratio, researchers consider the current ratio (CR). The results of the study prove that during the observation period the working capital turnover rate of PT. Pinago Utama Tbk based on cash turnover experienced a downward movement by an average of 26.17 times, but the working capital turnover rate based on account receivable turnover increased by an average of 5.29 times, then the working capital turnover rate was successively based on inventory turnover. and net working capital turnover experienced fluctuating movements with an average of 11.27 times and 5.073 times. The results also show the level of liquidity of PT. Pinago Utama Tbk during the observation period as seen from the current ratio showed a fluctuating movement with an average of 125%.